Plasmalogen as a Bioactive Lipid Drug: From Preclinical Research Challenges to Opportunities in Nanomedicine - Wu, Yu; Deng, Yuru; Angelov, Borislav; Angelova, Angelina (FASEB bioAdvances, 2025)
Plasmalogens are natural glycerophospholipids that account for approximately 15%-20% (mol%) of human tissues' cellular membrane phospholipid composition. They play an important role in lipid membrane organization and function, including acting as endogenous antioxidants. Plasmalogens contain a vinyl-ether linked alkyl chain at position sn-1, characteristic of vinyl-ether lipids, and often a polyunsaturated fatty acid (PUFA) acyl chain at position sn-2 of the glycerol backbone. The role of plasmalogens in various patho-physiological processes has been revealed in recent years, including various neurological disorders associated with plasmalogen deficiency. Plasmalogen Replacement Therapy (PRT) is a therapeutic approach that aims to increase plasmalogen levels in the body and address plasmalogen deficiencies in diseases such as age-related neurodegenerative diseases, cardiovascular diseases, certain genetic peroxisomal disorders, and metabolic disorders. We provide a detailed overview of current information on the role of plasmalogens in health and disease. We summarize various strategies for regulating plasmalogen levels and highlight recent advancements in therapeutic applications. We also focus on the potential application of nanomedicine for treating disorders associated with PUFA-lipid and plasmalogen deficiencies.
Keywords: PUFA‐plasmalogens; lipid replacement therapy; neuroregeneration; drug delivery; bioactive lipids; nanomedicine